PELATIHAN PEMBUATAN PUPUK KOMPOS PADAT LIMBAH KOTORAN AYAM - Nurlia; Royani, Novida (MONSU'ANI TANO Jurnal Pengabdian Masyarakat, 2024)
This community service activity aims to increase the understanding and skills of the people of Lontos Village in making compost made from chicken manure to improve agricultural output and the community's economy. The community service method is carried out in three stages; preparation stage, socialization and application stage, and final stage. The preparation stage is carried out in coordination with village officials. The socialization stage was carried out in community meetings and special socialization, as well as training in making compost from fermentation using EM4 and chicken manure. The final stage consists of creating a final report. The results obtained from this activity are that the people of Lontos Village are able to make solid compost fertilizer made from chicken manure which can be used in agriculture or commercialized so that it can improve the community's economy